Uniaxial compressive damage evolution and constitutive modeling of fissure-like rocks under different loading rates based on acoustic emission - Qinyong Wang; Wei Chen; Wenqing Peng; Yuanzeng Wang; Yu Zhou; Zhili Peng (Scientific Reports)
Abstract In natural environments, most rocks possess internal fissures and are often exposed to diverse external loads arising from engineering activities and ground stress, among other factors. This study aims to explore the influence of different loading rates on the mechanical properties and acoustic emission (AE) characteristics of fissured rocks and to develop an intrinsic damage model. To achieve this, prefabricated fissured rock specimens that mimic natural rocks were prepared. Uniaxial compression tests along with AE monitoring were carried out at various loading rates. Subsequently, a loss—damage constitutive model was developed, which describes the deformation and damage process of rocks based on the characterization of AE energy. The results are as follows: (1) Prefabricated fissured rock samples have lower strength compared to non-fissured rock samples due to the existence of prefabricated fissures. As the loading rate increases, both the peak strength and the elastic modulus increase. (2) Stress thresholds are significantly affected by the loading rate, showing a positive correlation. Prefabricated fissures reduce these thresholds, thus accelerating the damage process. (3) There is a strong correlation between AE characteristics and stress—strain curves. AE parameters, namely the number of rings, energy, and cumulative energy, go through three stages: calm development, active development, and surge development. The number of AE rings, energy, and cumulative energy are positively correlated with the loading rate, while the cumulative ringing counts decrease. (4) A damage constitutive model constructed with AE energy and the Logistic function can accurately represent the specimen’s response to different loading rates. This model closely matches the actual stress—strain curve, indicating improved accuracy and applicability.